Tracheal Atresia with Segmental Esophageal Duplication: An Unusual Anatomic Arrangement. (March 2016) - Gaerty, Kirsten; Thomas, Joseph T.; Petersen, Scott; Tan, Edwin; Kumar, Sailesh; Gardener, Glenn; Armes, Jane
An unusual anatomic configuration of segmental tracheal agenesis/atresia with esophageal duplication on autopsy in a fetus that demised in utero at 29 weeks is reported. The mother was scanned initially for a cardiac anomaly at 20 weeks and on follow-up scan at 27 weeks had polyhydramnios and underwent amnioreduction. The final autopsy diagnosis was vertebral, ano-rectal, cardiac, tracheoesophageal, renal, and limb malformations (VACTERL). We discuss the autopsy findings along with the embryological mechanisms and compare the configuration with Floyd's classification for tracheal agenesis. The difficulties in prenatal diagnosis are discussed.